PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN TEKNIK PAPER FOLDING UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF PESERTA DIDIK KELAS IV MATERI PECAHAN - Dean Nurmala SR; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Mathematics is often considered difficult, and negative perceptions of it can hinder students' interest and progress in learning it. Therefore, innovation in teaching methods is needed, such as the use of problem-based learning models assisted by paper folding techniques, to help students understand the concept of fractions better. The purpose of this research is to determine that the use of problem-based learning models assisted by paper folding techniques can improve the cognitive development of fourth-grade students in the material of fractions. This research uses a qualitative descriptive technique to describe the phenomena that occur. The results of this practice show that students can apply problem-based learning models assisted by paper folding techniques well, and the evaluation results show an increase in their understanding of the concept of fractions. Thus, this technique-assisted model can be an effective innovation in fraction learning, making mathematics learning more enjoyable and easier for students to understand.